2021
DOI: 10.1002/jcop.22554
|View full text |Cite
|
Sign up to set email alerts
|

Protective factors in preventing delinquency: Caregiver support, caregiver monitoring, and school engagement

Abstract: Youth who are potential victims of maltreatment are more likely to commit delinquent acts, which may lead to incarceration. Applying a resiliency framework may shift the focus to positive adaptation. For instance, protective mechanisms promote social, academic, and conduct competencies for at‐risk youth. This analysis estimated the protective effects of caregiver perceived support, and caregiver monitoring, and school engagement. It used delinquency as a measure of conduct competence. A latent variable structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
2
0
2
Order By: Relevance
“…Studies have shown that caregiver’s knowledge of adolescent’s behavior may act as a protective buffer against development of adolescent maladjustment behaviors, such as delinquency and antisocial problems, depressed mood, and self-esteem (Kerr & Stattin, 2000; Racz & McMahon, 2011; Sullivan et al, 2004). Interestingly, how parents acquire knowledge of adolescents’ behaviors is central to the protective influence of caregiver’s knowledge; with adolescent’s self-disclosure appearing to be a more prominent influence than parents’ own monitoring and soliciting behaviors (Kerr & Stattin, 2000; Lamari-Fisher & Bond, 2021; Racz & McMahon, 2011; Stattin & Kerr, 2000).…”
Section: Adverse Childhood Experiences Increase Risk For Exposure To ...mentioning
confidence: 99%
“…Studies have shown that caregiver’s knowledge of adolescent’s behavior may act as a protective buffer against development of adolescent maladjustment behaviors, such as delinquency and antisocial problems, depressed mood, and self-esteem (Kerr & Stattin, 2000; Racz & McMahon, 2011; Sullivan et al, 2004). Interestingly, how parents acquire knowledge of adolescents’ behaviors is central to the protective influence of caregiver’s knowledge; with adolescent’s self-disclosure appearing to be a more prominent influence than parents’ own monitoring and soliciting behaviors (Kerr & Stattin, 2000; Lamari-Fisher & Bond, 2021; Racz & McMahon, 2011; Stattin & Kerr, 2000).…”
Section: Adverse Childhood Experiences Increase Risk For Exposure To ...mentioning
confidence: 99%
“…Otros de los factores protectores que presentaron los dos hermanos resilientes fueron el continuar con sus estudios, tener aspiraciones, así como un soporte o apoyo dentro de la familia; en ambos casos se trata de la hermana mayor, quien resultó un modelo a seguir, esto se corrobora con lo encontrado en otros estudios (Barnert et al, 2021;Lamari-Fisher et al, 2021) Con respecto al área social, mencionaron conocer nuevos amigos de quienes reciben consejos. En el área de salud refirieron haber dejado de fumar o tomar.…”
Section: Conclusiones Y Discusiónunclassified
“…Entre esos factores se han encontrado los siguientes: grupos sociales (cambio elegido del grupo de amigos, es decir, abandonar a los amigos involucrados en la delincuencia), escuela (con un bajo número de alumnos desviados conductualmente, notas altas y tener planes a futuro de asistir a la universidad), supervisión y apoyo de los padres, interacciones positivas con los padres o cuidadores durante la infancia, percepción de la legitimidad de las autoridades legales, finalizar la escuela (el abandono de escuela, si va acompañado de un cambio hacia un empleo regular, puede suponer una reducción de las actividades delictivas), mudarse a otro lugar con menos índice de delincuencia, empleo (reduce actividades delictivas), matrimonio (se ha sugerido que las relaciones estables orientadas hacia el matrimonio proporcionan fuertes influencias hacia la conformidad y el cumplimiento de la ley; sin embargo, también se ha encontrado que el casarse desde muy joven puede estar asociado con la delincuencia), religiosidad, reconocimiento de la participación pro social, cambio de las circunstancias adversas, una buena amistad, buenas experiencias compensadoras, creación de nuevas oportunidades, mecanismos de afrontamiento (el afrontamiento debe tener la función dual de resolver los problemas sociales y de regular la angustia emocional). (Barnert et al, 2021;Lamari-Fisher et al, 2021;Florentini, 2021;Fointane et al, 2016;Hemphill et al, 2016;Rutter, 1988).…”
Section: Introductionunclassified
“…In contrast, harsh or inconsistent discipline may instill feelings of hostility and resentment in adolescents, increasing the propensity for aggressive responses to perceived threats or challenges (Bjørnebekk & Mørkrid Thøgersen, 2021). Moreover, parental monitoring and supervision play a crucial role in deterring involvement in delinquent activities and mitigating the risk of aggressive behavior among adolescents (Lamari-Fisher & Bond, 2021). By understanding the nuanced influences of parenting practices on adolescent aggression, interventions can be tailored to promote positive parenting strategies and strengthen parent-child relationships, ultimately fostering healthier developmental outcomes and reducing the prevalence of violence in communities.…”
mentioning
confidence: 99%